2007
DOI: 10.1089/pho.2007.2053
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Low-Level Laser Therapy in Temporomandibular Joint Disorders: A Placebo-Controlled Study

Abstract: The results suggest that LLLT (application of 10 J/cm(2) and 15 J/cm(2)) can be considered as a useful method for the treatment of TMD-related pain, especially long lasting pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
84
0
26

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 16 publications
9
84
0
26
Order By: Relevance
“…However, some studies have shown useful findings in treatment of dentin hypersensitivity, temporomandibular joint disorders, inferior alveolar nerve paraesthesia resulting from third molar surgery, sagittal osteotomy, trigeminal neuralgia, labial herpes, aphthous ulcers and post-chemotherapy and ray inflammation. [7][8][9][10][11][12] As there are conflicting findings regarding the effectiveness of low-level laser therapy (LLLT) and the importance of controlling third molar surgery's complications, this study aimed to assess the effect of LLLT on pain, swelling and maximum mouth opening in patients undergoing third molar surgery. In this study, we increased the number and variety of studied groups in order to reduce the error rate, in comparison to former researches.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown useful findings in treatment of dentin hypersensitivity, temporomandibular joint disorders, inferior alveolar nerve paraesthesia resulting from third molar surgery, sagittal osteotomy, trigeminal neuralgia, labial herpes, aphthous ulcers and post-chemotherapy and ray inflammation. [7][8][9][10][11][12] As there are conflicting findings regarding the effectiveness of low-level laser therapy (LLLT) and the importance of controlling third molar surgery's complications, this study aimed to assess the effect of LLLT on pain, swelling and maximum mouth opening in patients undergoing third molar surgery. In this study, we increased the number and variety of studied groups in order to reduce the error rate, in comparison to former researches.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported the efficacy of LLLT to be superior to placebo therapy [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and other physical therapies , while, others found no significant differences between LLLT and placebo for the measures of TMJ pain [24][25][26]. However there is an advantage of using LLLT in the treatment of TMDs as it is non-invasive, cost effective and does not have any known side effects.…”
Section: Introductionmentioning
confidence: 99%
“…They are reversible therapies mentioned in previous reports as the initial treatment for TMD (Bani & Bergamini, 2001;Fikácková et al;Naikmasur et al, 2008), and are effective in reducing pain and muscular tension. The laser protocol used in the present study was chosen in view to its ability to penetrate the muscle tissue, reducing pain and increasing active range of motion and according to our alterations, also similar to control group.…”
Section: Resultsmentioning
confidence: 99%